Mutations in oxyR Resulting in Peroxide Resistance in Xanthomonas campestris - Mongkolsuk, Skorn (American Society for Microbiology (ASM), 2000)
A spontaneous Xanthomonas campestris pv. phaseoli H(2)O(2)-resistant mutant emerged upon selection with 1 mM H(2)O(2). In this report, we show that growth of this mutant under noninducing conditions gave high levels of catalase, alkyl hydroperoxide reductase (AhpC and AhpF), and OxyR. The H(2)O(2) resistance phenotype was abolished in oxyR-minus derivatives of the mutant, suggesting that elevated levels and mutations in oxyR were responsible for the phenotype. Nucleotide sequence analysis of the oxyR mutant showed three nucleotide changes. These changes resulted in one silent mutation and two amino acid changes, one at a highly conserved location (G197 to D197) and the other at a nonconserved location (L301 to R301) in OxyR. Furthermore, these mutations in oxyR affected expression of genes in the oxyR regulon. Expression of an oxyR-regulated gene, ahpC, was used to monitor the redox state of OxyR. In the parental strain, a high level of wild-type OxyR repressed ahpC expression. By contrast, expression of oxyR5 from the X. campestris pv. phaseoli H(2)O(2)-resistant mutant and its derivative oxyR5G197D with a single-amino-acid change on expression vectors activated ahpC expression in the absence of inducer. The other single-amino-acid mutant derivative of oxyR5L301R had effects on ahpC expression similar to those of the wild-type oxyR. However, when the two single mutations were combined, as in oxyR5, these mutations had an additive effect on activation of ahpC expression.